2011
DOI: 10.1258/jtt.2010.100105
|View full text |Cite
|
Sign up to set email alerts
|

Telerehabilitation in stroke care – a systematic review

Abstract: We conducted a systematic review of telerehabilitation interventions in stroke care. The following databases were searched: Medline, Embase, DARE-NHSEED-HTA (INAHTA) and the Cochrane Library. Nine studies, all published after 2000, were included in the review. A wide variety of telemedicine interventions in post-stroke rehabilitation care was identified. Four studies had been carried out in the USA, two in the Netherlands, two in Italy and one in China. There were four randomized controlled trials and one qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
171
0
8

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 243 publications
(201 citation statements)
references
References 22 publications
11
171
0
8
Order By: Relevance
“…Improving access to rehabilitative care may reduce disparities for stroke survivors and caregivers facing financial or transportation-related challenges. While research on telerehabilitation is limited, there is increasing evidence supporting the need for telerehabilitation services, the development of telerehabilitation interventions, and support for people with disabling conditions that potentially limit access to rehabilitation services [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Improving access to rehabilitative care may reduce disparities for stroke survivors and caregivers facing financial or transportation-related challenges. While research on telerehabilitation is limited, there is increasing evidence supporting the need for telerehabilitation services, the development of telerehabilitation interventions, and support for people with disabling conditions that potentially limit access to rehabilitation services [6][7][8][9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1990s, many telerehabilitation programs have been developed for patients with brain injury 5,9,14,17,18,21) . Most of these programs have focused on rehabilitation of physical disability or speech impairment 5,9,13,14,17,18) .…”
Section: Discussionmentioning
confidence: 99%
“…Most of these programs have focused on rehabilitation of physical disability or speech impairment 5,9,13,14,17,18) . In contrast, only a few studies have reported on telerehabilitation for cognition 7,8,10) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent review (Johansson, 2010), only very limited amount of ICT-supported treatments were available. Of the nine studies included in the review, four studies focused on a teleconsultation service for stroke patients.…”
Section: Introductionmentioning
confidence: 99%